ANTIMICROBIAL EFFECT OF ARROWROOT (Maranta arundinacea L.) METHANOLIC EXTRACT AGAINST Staphylococcus aureus BACTERIAL GROWTH - Syahputra, Muhammad Ghaza; Antari, Arlita Leniseptaria; Winarto, Winarto; Lestari, Endang Sri (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Introduction: Staphylococcus aureus is a spherical gram-positive bacterium that forms clusters and is frequently resistant to antibiotics. Methicillin-Resistant Staphylococcus aureus (MRSA) is a strain of S. aureus that is resistant to beta-lactam and cephalosporin groups of antibiotics, it is one of the biggest problems in resistant bacteria. Plants that have flavonoids in their extract can inhibit the growth of bacteria by impairing their cytoplasmic membrane. Arrowroot is an example of plants that have flavonoids in their extracts. Objectives: This research aims to determine the antimicrobial effect of arrowroot (Maranta arundinacea L.) methanolic extract against the growth of Staphylococcus aureus in vitro. Methods: This is true experimental research with a post-test control group design with two control groups and eight experimental groups. The sample of this research utilizes the MRSA strain of S. aureus received from the Microbiology Laboratory of Diponegoro University Faculty of Medicine that was eligible with the inclusion criteria. The research was conducted by using arrowroot extract concentrations 6.5%, 12.5%, 25%, 50%, and 100% to determine the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), and inhibitory zone diameter. Results: MIC and MBC of arrowroot methanolic extract against MRSA is 100%. The arrowroot methanolic extract to have yielded an inhibitory zone diameter is 100% with a mean inhibitory zone diameter of 15.5mm. Conclusion: Arrowroot methanolic extract can inhibit the bacterial growth of MRSAKeywords: Staphylococcus aureus, growth, M. arundinacea L. methanolic extract